2021
DOI: 10.3389/fphar.2020.583450
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Herbal Medicine Used With or Without Conventional Western Therapy for COVID-19: An Evidence Review of Clinical Studies

Abstract: Objective: To present the evidence of the therapeutic effects and safety of Chinese herbal medicine (CHM) used with or without conventional western therapy for COVID-19.Methods: Clinical studies on the therapeutic effects and safety of CHM for COVID-19 were included. We summarized the general characteristics of included studies, evaluated methodological quality of randomized controlled trials (RCTs) using the Cochrane risk of bias tool, analyzed the use of CHM, used Revman 5.4 software to present the risk rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 60 publications
0
11
0
1
Order By: Relevance
“…In order to complete this review as soon as possible without compromising the quality of our research, this rapid review was carried out on the basis of our previous research, 27 an evidence review of clinical studies regarding CHM for COVID-19. In the previous research, 27 we systematically searched for clinical trials of CHM which included oral CPM, Chinese herbal medicine injection and prescribed herbal decoctions used for COVID-19. We screened studies included in the previous research 27 to identify RCTs that only use oral CPM for COVID-19.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to complete this review as soon as possible without compromising the quality of our research, this rapid review was carried out on the basis of our previous research, 27 an evidence review of clinical studies regarding CHM for COVID-19. In the previous research, 27 we systematically searched for clinical trials of CHM which included oral CPM, Chinese herbal medicine injection and prescribed herbal decoctions used for COVID-19. We screened studies included in the previous research 27 to identify RCTs that only use oral CPM for COVID-19.…”
Section: Methodsmentioning
confidence: 99%
“…In the previous research, 27 we systematically searched for clinical trials of CHM which included oral CPM, Chinese herbal medicine injection and prescribed herbal decoctions used for COVID-19. We screened studies included in the previous research 27 to identify RCTs that only use oral CPM for COVID-19. Since the previous search date was up to April 30 th , 2020, the official start date of this rapid review was November 2 nd , 2020, we updated and searched for publications during the period between April 30 th , 2020 and November 2 nd , 2020.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with the conventional Western medicine-treated group, patients in the TCM-treated group showed significant improvements in lung computed tomography, clinical cure rate, ranging from mild to critical cases, length of hospital stay, total score of clinical symptoms and inflammatory biomarkers, with no evidence of severe adverse effects, discomfort or abnormal liver and kidney function [180] . Furthermore, a recent review of clinical studies suggested that TCM in combination with conventional Western treatment may be superior than conventional Western therapy alone in shortening the duration of main symptoms, reducing the aggravation rate and increasing the recovery rate [181] . Consistently, the combination of Chinese and Western medicines appears to be the mainstream for treatment of COVID-19 in China [182] .…”
Section: Traditional Chinese Medicine and Covid-19mentioning
confidence: 99%
“…In the previous research, 27 we systematically searched for clinical trials of CHM which included oral CPM, Chinese herbal medicine injection and prescribed herbal decoctions used for COVID-19. We screened studies included in the previous research 27 to identify RCTs that only use oral CPM for COVID-19. Since the previous search date was up to April 30th, 2020, the official start date of this rapid review was November 2nd, 2020, we updated and searched for publications during the period between April 30th, 2020 and November 2nd, 2020.…”
Section: Retrieval Platforms and Search Strategies Of Studiesmentioning
confidence: 99%